(untitled) (Publicaciones en Ciencias y Tecnología, 2011)
The information and communication technology (ICT‘s) are used by the organizations in order to facilitate the administration and control of their internal processes. The principal guideline is to achieve the linkage between business strategies and ICTs strategies. Taking this premise as our starting-point, the general objective of this article is to present the results of the application of the COBIT framework (Control Objectives for Information and Related Technology) in the monitoring process of the financial, countable and administrative data electronic interchange of the "Lácteos Los Andes" Western Region Controllership and Administration Unit. The mentioned process is critical for the organization on account of the value of the information transferred for the preparation of management reports. This study is a feasible project, which takes into account the knowledge application through a framework related to ICTs resources management.